Evaluation of The Connection Between the Intensity of Non-Alcoholic Fatty Liver Disease (Nafld) And Respiratory Performance Among a Cohort of Individuals Gathered from The Adiwaniyah Region, Iraq: A Cross-Sectional Exploration - Jabbar Dibby, Huda; Abdulaali Al-Mudhafar, Zahraa (Journal of Neonatal Surgery, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) stands as a prevalent culprit of chronic liver ailments across the globe. In the realm of NASH, the accumulation of fat in the liver is intertwined with inflammatory responses and cell death, potentially paving the way to fibrosis and cirrhosis. The delicate balance of pulmonary function can be swayed by a myriad of inherent (age, sex, ethnicity) and external (air pollution, smoking, biomass) influences. Moreover, its capability is compromised in diseases that affect areas beyond the lungs, such as cardiovascular disorders and chronic kidney issues. Notably, diminished pulmonary function has also been linked to the presence of nonalcoholic fatty liver disease (NAFLD). Aim of the study: The aim of this study is to assess the severity of non-alcoholic fatty liver disease (NAFLD) in a sample of Iraqi patients using fibrsocan and correlate the severity to pulmonary function. Patients and methods: The present investigation is a cross-sectional design that encompassed 124 individuals exhibiting clinical, laboratory, and imaging signs indicative of NAFLD, all of whom were enlisted from the gastroenterology hub at Al-Diwaniyah Teaching Hospital in Al-Diwaniyah, Iraq, during the timeframe spanning from February 2023 to April 2024. A Fibro scan (Fibroscan 530 compact, Echosense, Paris, France) was employed, with a skilled gastroenterologist overseeing the assessment of liver fibrosis and steatosis. For every participant enrolled in the research, spirometry was conducted utilizing the Cardio Touch - 3000 (Korea). The subsequent parameters were recorded: Forced Vital Capacity (FVC) and Forced Expiratory Volume in the first second (FEV1). Results: The patients were categorized as follows: 26 individuals exhibited Normal (Fibrosis score 0), representing 21.0 %; 44 individuals showed Mild (Fibrosis score 1), comprising 35.5 %; 23 individuals were classified as Moderate (Fibrosis score 2), accounting for 18.5 %, while 31 individuals fell into the Severe category (Fibrosis score 3), making up 25.0 %. The interplay between pulmonary function tests and non-alcoholic fatty liver disease (NAFLD) was assessed according to fibroscan outcomes, revealing that 90 patients demonstrated normal function, while 34 patients exhibited a restrictive pattern, with a notable correlation between the escalating severity of liver fibrosis and the prevalence of restrictive patterns among patients (p = 0.003). Conclusion: A significant proportion of patients with NAFLD have in addition impaired pulmonary function mostly in the form of restrictive changes and these changes are more frequently seen with increasing degree of liver fibrosis as indicated by fibroscan technique.